2014
DOI: 10.3109/01443615.2014.920791
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ramadan fasting on LH, FSH, oestrogen, progesterone and leptin in pregnant women

Abstract: Many pregnant Muslim women fast during Ramadan. Leptin has an important role in the reproductive system and hormones. In this study, FSH, LH, oestrogen, progesterone and leptin were measured in the first, second and fourth week of Ramadan and the second week post-Ramadan, in 30 fasting pregnant women. Data were analysed using repeated measures ANOVA by SPSS. The weight and BMI did not change during the study. A significant change in FSH, oestrogen, progesterone and leptin was observed (p < 0.05). The lowest va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…There have recently been a growing number of studies into the possible health effects of Ramadan during pregnancy. The dietary intake and weight gain of fasting pregnant women are reduced, 14,15 and fasting has been associated with several metabolic alterations including reduction in serum glucose, insulin, lactate, and carnitine levels, as well as elevation in serum triglyceride, cortisol, and leptin concentrations. 14,15 Most previous studies on Ramadan and birth outcomes were small and included only births within a limited time period, which allowed for only a limited correction for the confounding effects of seasonality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have recently been a growing number of studies into the possible health effects of Ramadan during pregnancy. The dietary intake and weight gain of fasting pregnant women are reduced, 14,15 and fasting has been associated with several metabolic alterations including reduction in serum glucose, insulin, lactate, and carnitine levels, as well as elevation in serum triglyceride, cortisol, and leptin concentrations. 14,15 Most previous studies on Ramadan and birth outcomes were small and included only births within a limited time period, which allowed for only a limited correction for the confounding effects of seasonality.…”
Section: Introductionmentioning
confidence: 99%
“…The dietary intake and weight gain of fasting pregnant women are reduced, 14,15 and fasting has been associated with several metabolic alterations including reduction in serum glucose, insulin, lactate, and carnitine levels, as well as elevation in serum triglyceride, cortisol, and leptin concentrations. 14,15 Most previous studies on Ramadan and birth outcomes were small and included only births within a limited time period, which allowed for only a limited correction for the confounding effects of seasonality. In the present study, we use data from a nationwide registry over an 11-year time period to evaluate birth outcomes of all babies born to mothers of Turkish and Moroccan descent (grouped together under the label "Mediterranean") in the Netherlands whose pregnancies overlapped with Ramadan, irrespective of lifestyle changes.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them did not show any detrimental effects of fasting in healthy women or on the neonatal outcome [16] [17]. Other studies reported that Ramadan fasting during pregnancy might have potential risks [18]. A later study confirmed that menstrual abnormalities, including oligomenorrhoea, polymenorrhoea, and hypermenorrhoea, increase during Ramadan, especially in participants who fasted more than 15 days [19].…”
Section: Discussionmentioning
confidence: 98%
“…Another condition of religious fasting during the holy month of Ramadan, may pose risks to pregnant women. In a sample of 30 fasting pregnant women, Khoshdel and colleagues measured significant changes in follicle stimulating hormone (FSH), estrogen, progesterone and leptin levels ( p < 0.05) [ 68 ]. Additionally, poor weight gain in the pregnant fasted women was observed during the study [ 68 ].…”
Section: Weight Loss During Pregnancymentioning
confidence: 99%
“…In a sample of 30 fasting pregnant women, Khoshdel and colleagues measured significant changes in follicle stimulating hormone (FSH), estrogen, progesterone and leptin levels ( p < 0.05) [ 68 ]. Additionally, poor weight gain in the pregnant fasted women was observed during the study [ 68 ]. In another study, Ziaee and colleagues studied a historical cohort of pregnant women seen at Tehran hospitals at one of the trimesters in the holy month of Ramadan [ 69 ].…”
Section: Weight Loss During Pregnancymentioning
confidence: 99%